Cwlwm - Enlli, Ffion (Y Lolfa, 2022)
Living in London, Lydia is struggling through her twenties, regretting drunken nights, reflecting on texts and trying her best nor to be late for work. She has a complicated relationship with Wales. Far from home, she questions her identity and her vision of herself as a Welsh woman in the world.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books